Effect of women's political inclusion on the level of infrastructures in Africa - Tii Njivukuh Nchofoung; Simplice Asongu; Vanessa Tchamyou (African Governance and Development Institute (AGDI), 2022)
The need for gender inclusion was highlighted as the fifth sustainable development goal (SDG) (i.e. SDG5) and policies have been gearing towards attaining this objective and its subsequent effect on macroeconomic outcome. Equally, the demonstrated trend of infrastructures in Africa in terms of stocks and future need is unique compared to the rest of the world. The objective of this study is therefore to empirically examine the effect of women's political inclusion on infrastructural development in Africa. The results through the system GMM and Quantile Regression techniques show that women's political inclusion enhances infrastructural development in Africa. The result is robust across different measures of infrastructures and political inclusion. Besides, the positive relationship is maintained across income groups, levels of political stability and export structure. However, the effect is non-significant in countries with infrastructural scores around the extreme quantiles. The results of the study recommend African policymakers to prioritise the inclusion of women in the political agenda as one of the strategies towards the development of infrastructures. This could come through the putting in place of laws that favour women's participation in politics. Moreover, the countries should ratify international conventions that favour gender inclusion.
Keywords: 330; Infrastructures; Women's political empowerment; Africa